THE ROLE OF INFORMATION TECHNOLOGY, EMPLOYEE TRAINING AND SERVICE QUALITY IN IMPROVING PATIENT SATISFACTION - Fajar Wahyudi; Vip Paramarta; Alexandra DeSousa Guterres (RADJA PUBLIKA, 2025)
The healthcare industry is undergoing a significant transformation due to technological advances and public demand for better services. This study aims to examine the role of information technology, employee training, and service quality in improving patient satisfaction. Information technology, such as electronic medical records and telemedicine, improves service efficiency and access to medical information. Employee training, both technical and communication skills, contribute to improving the competence of medical and non-medical personnel in providing responsive and empathetic services. Service quality, including speed, accuracy, friendliness, and convenience of facilities, is also an important factor in influencing patient satisfaction. This research used a literature review approach, collecting data from various scientific articles, journals, and related publications. The results showed that a combination of the three factors - information technology, training, and service quality - plays an important role in improving patient satisfaction. The study also identified challenges in the implementation of health service improvement strategies and provided recommendations for the development of more innovative and patient-oriented services.